Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Annisaa Mahirah; Irwati; Uzliawati, Lia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze the effect of profitability and firm size on firm value. Firm value is a dependent variable that can be influenced by profitability and firm size. The sample selection method is purposive sampling. The type of data is quantitative and the secondary data source is taken from the company's financial statements and annual statistical reports. The data collection technique used is the documentation technique from the official IDX website. The findings of profitability have a significant positive effect on firm value in line with signal theory. Meanwhile, firm size has a significant negative effect on firm value, not in line with signal theory.